Role of the Melanocortin System in the Central Regulation of Cardiovascular Functions - Copperi, Francesca; Kim, Jung Dae; Diano, Sabrina (Frontiers in Physiology, 2021)
Increasing evidence indicates that the melanocortin system is not only a central player in energy homeostasis, food intake and glucose level regulation, but also in the modulation of cardiovascular functions, such as blood pressure and heart rate. The melanocortins, and in particular α- and γ-MSH, have been shown to exert their cardiovascular activity both at the central nervous system level and at the periphery (e.g. in the adrenal gland), binding their receptors MC3R and MC4R and influencing the activity of the sympathetic nervous system. In addition, some studies have shown that the activation of MC3R and MC4R by their endogenous ligands is able to improve the outcome of cardiovascular diseases, such as myocardial and cerebral ischemia. In this brief review, we will discuss the current knowledge of how the melanocortin system influences essential cardiovascular functions, such as blood pressure and heart rate, and its protective role in ischemic events, with particular focus on the central regulation of such mechanisms.